2017
DOI: 10.3389/fphar.2017.00346
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Steroid Uptake and Intracrine Action in Endometrial and Ovarian Cancers

Abstract: Endometrial and ovarian cancers predominately affect women after menopause, and are more frequently observed in developed countries. These are considered to be hormone-dependent cancers, as steroid hormones, and estrogens in particular, have roles in their onset and progression. After the production of estrogens in the ovary has ceased, estrogen synthesis occurs in peripheral tissues. This depends on the cellular uptake of estrone-sulfate and dehydroepiandrosterone-sulfate, as the most important steroid precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 179 publications
(243 reference statements)
2
31
2
2
Order By: Relevance
“…Based on our data, BSP may also interfere with OATP1A2 and OATP1C1 function in vivo (serum concentrations can reach 3 µ m ); however, BSP is no longer used in liver function tests for humans . On the other hand, in vivo ES plasma concentrations are in the nanomolar range ; therefore, the in vivo relevance of OATP1A2 or OATP1C1 in ES transport may be less relevant. Similarly, the inhibitory effect of verapamil on OATP1A2 function may be negligible in vivo, since the maximal in vivo verapamil concentration is 0.21 µ m in contrast to the measured IC 50 of 7.18 µ m .…”
Section: Discussionmentioning
confidence: 93%
“…Based on our data, BSP may also interfere with OATP1A2 and OATP1C1 function in vivo (serum concentrations can reach 3 µ m ); however, BSP is no longer used in liver function tests for humans . On the other hand, in vivo ES plasma concentrations are in the nanomolar range ; therefore, the in vivo relevance of OATP1A2 or OATP1C1 in ES transport may be less relevant. Similarly, the inhibitory effect of verapamil on OATP1A2 function may be negligible in vivo, since the maximal in vivo verapamil concentration is 0.21 µ m in contrast to the measured IC 50 of 7.18 µ m .…”
Section: Discussionmentioning
confidence: 93%
“…Drug development and potential therapeutic approaches are discussed. In this review, the enzymes involved in steroid deactivation/clearance (Rižner, 2013 , 2016 ; with the exclusion of steroid sulphotransferases) and those involved in the transport of conjugated steroids through the plasma membrane (Rižner et al, 2017 ) are not described. Studies on serum/tissue steroid levels are reported and discussed only if based on gold standard GC/LC-MS.…”
Section: Introductionmentioning
confidence: 99%
“…Однако некоторые изоформы ERβ, такие как ERβ5, могут действовать и как онкоген [16]. Согласно гипотезе «несостоятельности эстрогенов», воздействие эндогенных или экзогенных эстрогенов в отсутствие действия андрогенов и прогестинов увеличивает пролиферацию и одновременные ошибки репликации ДНК, что приводит к соматическим мутациям и злокачественным трансформациям [1,17,18]. Подобные изменения могут быть одним из факторов, способствующих модификации злокачественного процесса, в частности у животных с хронической нейрогенной болью.…”
Section: заключениеunclassified
“…Стероидные гормоны играют важную роль в физиологии человека, а нарушение андрогенных, эстрогенных и прогестеронных воздействий связано с развитием различных видов как злокачественных, так и доброкачественных пролиферативных заболеваний [1]. Установлена важная роль локального синтеза половых стероидов за счет наличия ферментов CYP11A1 и CYP17A1 в периферических тканях, что дает возможность автономной регуляции пролиферативных процессов, включая доброкачественные и злокачественные опухоли [2].…”
unclassified